Assessment of natural radioactivity levels in widely used food spices in the Iraqi Kurdistan region and their associated radiological risks - Sabr, Barzan; Salih Omer Haji; Azeez, Hiwa; Mohammed Issa Hussein; Jahfer Majeed Smail (Zanco Journal of Pure and Applied Sciences, 2023)
In this research, the activity concentration of naturally occurring radioactive nuclides in 19 widely consumed spices in the Iraqi Kurdistan Region was determined. For the radioactivity evaluation, gamma-ray spectrometry equipment with high purity-germanium detectors (HP-Ge) was utilized. The activity concentrations of 226Ra, 232Th, 40K, and 137Cs ranged from BMDA (Below Minimum Detectable Activity) (for cumin) to 4.65 ± 0.37 Bq.Kg-1 (for learners), 0.06 ± 0.02 (for ring) to 3.79 ± 0.26 Bq.Kg-1 (learners), 37.8 ± 2.09 (for ring) to 869.95 ± 36.92 Bq.Kg-1 (for turmeric), and BMDA to 1.83 ± 0.63 Bq.Kg-1 (for cloves), respectively. On the basis of these results, the radiological hazard indices associated with the use of food spices were calculated. The total ingestion annual effective dose (IAED) of 226Ra, 232Th, and 40K ranged between 0.25 and 5.66 µSv.y-1. The dose of naturally occurring radionuclides was less than the recommended limit, and there are no radiological risks associated with the consumption of food spices. This sort of baseline information will very probably be crucial for estimating population exposure.